Fishing Gear and Methods of the River Brahmaputra in Assam - Joseph, K M; Narayanan, K P (Fishery Technology, 1965)
Potentially the inland fishery resources of the country are of very high order. But the present Â·level of their exploitation is far from optimum, mainly because of the inade. quacies of the existing fishing gear and methods. There is vast scope for increasing the fish production from inland waters by improving the existing gear and methods. This would require a thorough study of the fishing gear and methods in vogue, of which very little is known at present. In the present communication the authors discuss the fishing gear and methods of the river Brahmaputra, in Assam, based on a survey carried out by them during January- February 1964. The survey covers a 640 km stretch of the Brahmaputra river, its important tributaries and connected bheels, from Dhubri to Dibrugarh. As a result of the survey about 19 types of fishing nets, which could be grouped into eight classes, were identified. The salient technological features of the gears and their methods of operation are discussed class-wise. The characteristics of the individual types are shown in tables. The materials used for gear and gear accessories, are briefly discussed. The classification and relative importance of difierent types of gear are examined. Besides, the influence of the ecological and topographical features of the river on the development of different types of fishing gear, is also discussed.